The effects of manager role stress on job thriving of both employees and managers through empowering leadership. (October 2022) - Lin, Meizhen; Ling, Qian; Zhang, Lianyu; Cui, Xiangtian; Zhang, Zhengjie
Abstract: Using a sequential mixed methods approach, we comprehensively explore the influence of manager role overload (MRO) and manager role ambiguity (MRA) on job thriving of both managers and employees. Study 1 was based on a quantitative survey design. We collected nested data from 675 valid employee–department manager pairs from 92 departments in 28 hotels in China. The findings suggest that both MRO and MRA hinder empowering leadership, in turn impairing the job thriving of both managers and employees. However, the negative effect of MRO on empowering leadership disappears when managers have a high level of trust in employees. Study 2 entailed in-depth interviews of 15 middle managers from 11 hotels to further explain why and when MRO and MRA obstruct empowering leadership.